A retrospective study of adult patients with noncirrhotic hyperammonemia. Issue 6 (16th August 2020) - Stergachis, Andrew B.; Mogensen, Kris M.; Khoury, Charbel C.; Lin, Alexander P.; Peake, Roy WA.; Baker, Joshua J.; Barkoudah, Ebrahim; Sahai, Inderneel; Sweetser, David A.; Berry, Gerard T.; Krier, Joel B.
Abstract: Adult‐onset noncirrhotic hyperammonemia (NCH) is poorly understood and has a high morbidity and mortality. To elucidate the etiology and management of NCH, we performed a retrospective analysis of 23 adults (median age 51) with NCH treated between 2014 and 2020 at two academic medical centers. Hyperammonemia was diagnosed in all cases during the evaluation of altered mental status, with 22% presenting with seizures. Peak ammonia levels were >200 μmol/L in 70% of cases. Defects in ammonia metabolism were assessed using urea cycle biochemical testing, germline genetic testing, and testing for urease‐producing infectious agents. Ammonia metabolism defects in these cases appear attributable to four major sources: (a) infection with urease‐producing organism (n = 5); (b) previously undiagnosed inborn errors of metabolism (IEMs) (n = 4); (c) clinical exposures causing acquired urea cycle dysfunction (n = 6); and (d) unexplained acquired urea cycle dysfunction (uaUCD) (n = 8), as evidenced by biochemical signatures of urea cycle dysfunction without a genetic or clinical exposure. Severe protein malnutrition appeared to be a reversible risk factor for uaUCD. Overall, 13% of our cohort died prior to resolution of hyperammonemia, 26% died after hyperammonemia resolution, 57% survived after having reversible neurological changes, and 4% survived with irreversible neurological changes. Renal replacement therapy for ammonia clearance was often utilized for patients with an ammonia level above 250 μmol/L and patients were frequently empirically treated with antibiotics targeting urea‐splitting organisms. Our study demonstrates that acquired urea cycle dysfunction, IEMs and urease‐producing infections are major sources of adult‐onset NCH and highlights successful management strategies for adult‐onset NCH. Concise summary: In this retrospective cohort study of 23 patients with adult‐onset noncirrhotic hyperammonemia (NCH), we identify acquired urea cycle dysfunction, inborn errors of metabolism, and urease‐producing infections as the three major sources of NCH and highlight successful management strategies.